Mesoporous Silica Loaded with Molybdenum Phosphide Nanoparticles for Hydrogen Evolution - Keliang Wang; Chan Jiang; Zhouyang Chen; Shaojie Ma (Advances in Materials Science and Engineering)
A mesoporous silica loaded with molybdenum phosphide nanoparticles (MoP@MSN) was synthesized using Pluronic F-127 as a hard template. Using the method of XRD and HRTEM, the crystallinity, the phase structure, and the morphologies of the MoP@MSN were investigated. The results showed that the MoP@MSN were composed of nanoflakes with approximately 100 nm. Through the linear sweep voltammetry (LSV), the Tafel slopes of 100 and 341 mV were yielded for MoP@MSN and pure MoP, respectively, meaning that the composite of MSN can significantly improve the conductivity of the products. Meanwhile, the mesoporous MoP@MSN presented excellent electrochemical activity and stability toward hydrogen evolution compared with those of bulk MoP nanoparticles, showing a promising prospect in hydrogen production.